Formation of carbon–nitrogen bonds in carbon monoxide electrolysis - Jouny, Matthew; Lv, Jing-Jing; Cheng, Tao; Ko, Byung Hee; Zhu, Jun-Jie; Goddard, William A.; Jiao, Feng (Nature chemistry, 2019)
The electroreduction of CO 2 is a promising technology for carbon utilization. Although electrolysis of CO 2 or CO 2 -derived CO can generate important industrial multicarbon feedstocks such as ethylene, ethanol, n -propanol and acetate, most efforts have been devoted to promoting C–C bond formation. Here, we demonstrate that C–N bonds can be formed through co-electrolysis of CO and NH 3 with acetamide selectivity of nearly 40% at industrially relevant reaction rates. Full-solvent quantum mechanical calculations show that acetamide forms through nucleophilic addition of NH 3 to a surface-bound ketene intermediate, a step that is in competition with OH – addition, which leads to acetate. The C–N formation mechanism was successfully extended to a series of amide products through amine nucleophilic attack on the ketene intermediate. This strategy enables us to form carbon–heteroatom bonds through the electroreduction of CO, expanding the scope of products available from CO 2 reduction. The electroreduction of CO 2 -derived CO is a promising technology for the sustainable production of value-added chemicals. Now, it is shown how C–N bonds can be formed electrochemically through CO electroreduction on a Cu surface in the presence of amines. The formation of acetamides is observed through nucleophilic addition to a ketene intermediate.